2012
DOI: 10.1371/journal.pone.0038554
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Adjustments in Drought Tolerant and Sensitive Soybean Genotypes in Response to Water Stress

Abstract: Soybean (Glycine max L.) is an important source of protein for human and animal nutrition, as well as a major source of vegetable oil. The soybean crop requires adequate water all through its growth period to attain its yield potential, and the lack of soil moisture at critical stages of growth profoundly impacts the productivity. In this study, utilizing 1H NMR-based metabolite analysis combined with the physiological studies we assessed the effects of short-term water stress on overall growth, nitrogen fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
167
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(195 citation statements)
references
References 46 publications
20
167
1
7
Order By: Relevance
“…Similar results was also observed by Ashraf and Iram (2005) in Phaseolus vulgaris. Accumulation of proline under stress in many plant species has been correlated with stress tolerance, and its concentration usually higher in stress tolerant than in stress sensitive plants (Silvente et al, 2012). Significant differences in proline content were observed among genotypes under water stress (Fig 1).…”
Section: Proline Accumulationmentioning
confidence: 97%
“…Similar results was also observed by Ashraf and Iram (2005) in Phaseolus vulgaris. Accumulation of proline under stress in many plant species has been correlated with stress tolerance, and its concentration usually higher in stress tolerant than in stress sensitive plants (Silvente et al, 2012). Significant differences in proline content were observed among genotypes under water stress (Fig 1).…”
Section: Proline Accumulationmentioning
confidence: 97%
“…It was reported that the physiological processes influenced by drought can be identified by the biochemical characterization of plant tissues under stress conditions [46]. Limited research was conducted to characterize the biochemical compounds such as protein, amino acids, carbohydrates, and phenolics in the breeding program as a tool for selection, but this tool has promise in selecting for abiotic stress tolerance [24,47].…”
Section: Soybean -The Basis Of Yield Biomass and Productivity 146mentioning
confidence: 99%
“…Biological multivariate data generated from metabolomic studies are commonly analyzed using principal component analysis (PCA) [202], partial least square (PLS) [203], and orthogonal projections to latent structures (O-PLS) [203,204]. Numerous metabolomic studies have been done on crops under stress, including: salinity [215][216][217], drought [218][219][220][221], flooding [222], ozone treatment [223], fungal infections [224][225][226], bacterial infections [217,227], other infections [228], and multiple stresses [229,230].…”
Section: Phenomementioning
confidence: 99%
“…Signal patterns must be matched to known standards or depositions in the databases in order to identify the actual compounds. For example, the accumulation of compatible solutes, such as proline, glycine-betaine, and their precursors, is usually observed in osmotically stressed crops, especially in tolerant varieties [216,220,221]. A specific example is the mitochondrial metabolic profile of flood-stressed soybean; metabolites were extracted from the roots and hypocotyls of soybean seedlings with or without submergence stress [226], and were then analyzed using capillary electrophoresis mass spectrometry.…”
Section: Phenomementioning
confidence: 99%